Selection of Yeasts Antagonists as Biocontrol Agent of Mango Fruit Rot caused by Botryodiplodia theobromae - DWI SUGIPRIHATINI; SURYO WIYONO; . WIDODO (Indonesian Society for microbiology, 2011)
Fruit rot caused by Botryodiplodia theobromae is one of the most important post harvest disease of mango in Indonesia. Study on biological control on the disease is required to develop environmentally-sound control technology. The research objectives were to study the potency of yeasts in controlling post harvest mango disease i.e. fruit rot caused by B. theobromae and mechanism involve in the biocontrol. Total yeast isolates used for screening were twenty one, four from collection of Plant Clinic of Institut Pertanian Bogor, and twenty one isolated from healthy mango skin. All of yeast isolates were characterized and identified using BIOLOG. Bioassay on antagonistic activity of yeasts against fruit rot, in-vitro dual culture test and chitinolytic activity were carried out. Cryptococcus albidus var. aerius WSW1, Pichia guilliermondii K1, and Debaryomyces hansenii K12 were the three most effective antagonistic yeasts against B. theobromae with effectiveness of 70.83%, 45.83%, 37.50% respectively. In vitro bio-assay showed that C. albidus var. aerius WSW1, C. albidus WSW2, C. albidus K6, C. terreus YSW1, Candida edax OSW1, Candida edax K13, and Cryptococcus luteolus K2 had high antibiosis activity. Biocontrol activity of tested yeasts against fruit rot of mango did not correlate to its antibiosis and chitinolytic activity